2020
DOI: 10.1002/adom.202000507
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone‐Based Luminescent Thermometry via Temperature‐Sensitive Delayed Fluorescence from Gd2O2S:Eu3+

Abstract: Thermal images generated from infrared radiation are useful for monitoring many processes; however, infrared cameras are orders of magnitude more expensive than their visible counterparts. Methods that allow visible cameras to capture thermal images are therefore of interest. In this contribution, thermal images of a surface coated with an inexpensive inorganic micropowder phosphor are generated from the analysis of a video taken with a smartphone camera. The phosphor is designed to have a temperature‐dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 51 publications
0
42
0
Order By: Relevance
“…The bulky and expensive equipment needed to image of such nano- to micro-second lifetimes can be avoided by shifting the lifetimes of the labels to the 100 ms to 10 s range 25 . The upper limit on lifetime here is imposed to allow sufficiently rapid authentication, limiting the charging time and video recording time such that authentication can be completed within around 15–20 s. Such extension in the PL lifetime would allow the use of a video captured with a standard camera, such as those in smartphones, to characterize the lifetimes and provide a series of images at different lifetimes 25 27 . Several phosphors exhibiting persistent color change have been explored, but, to date, tailoring lifetimes to create a materials palette optimized for smartphone excitation and detection has not been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…The bulky and expensive equipment needed to image of such nano- to micro-second lifetimes can be avoided by shifting the lifetimes of the labels to the 100 ms to 10 s range 25 . The upper limit on lifetime here is imposed to allow sufficiently rapid authentication, limiting the charging time and video recording time such that authentication can be completed within around 15–20 s. Such extension in the PL lifetime would allow the use of a video captured with a standard camera, such as those in smartphones, to characterize the lifetimes and provide a series of images at different lifetimes 25 27 . Several phosphors exhibiting persistent color change have been explored, but, to date, tailoring lifetimes to create a materials palette optimized for smartphone excitation and detection has not been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…5 Unfortunately, in this case, the commonly obtained thermometer sensitivities to temperature changes are much lower than in the case of the luminescence intensity ratio counterparts. 5,[16][17][18]31,32 Therefore, extensive research is ongoing to develop new phosphors and/or to thermally activate different physical processes taking place in them to improve the sensitivity of lifetime-based luminescent thermometers. Recently, it has been shown that the SrTiO 3 :Mn 4+ nanocrystals show favourable thermometric properties not only in the LIR approach but also in the lifetime-based approach.…”
Section: Introductionmentioning
confidence: 99%
“…[ 42 ] Figure a (and Table S2, Supporting Information) shows examples of the largest S r values ( S m ) reported for ratiometric (hollow symbols) luminescent thermometers with an operating range compatible with m Optical sensing and for smartphone‐based luminescence thermometry (solid symbols). [ 46,55,59,66–89 ] The S r values for primary luminescent thermometers are shown in Figure 3b. [ 43,53,58–64 ] Noticeable, only one example refers to smartphone‐based luminescence thermometry, and presents the largest S r value.…”
Section: Optical Temperature Sensors Overviewmentioning
confidence: 99%
“…This approach includes a smartphone and although the analyses and excitation are externally provided, it is an important step toward m Optical sensing for IoT, as smartphones are widely available and easily accessible equipment for science and engineering to use. [ 83 ]…”
Section: Optical Temperature Sensors For the Iotmentioning
confidence: 99%